Comparative Study of Different Mesh Types in Hernia Repair: Compare the Outcomes, Complications, and Recurrence Rates of Different Mesh Types Used in Hernia Repair - Hassan, Syed Ahmed; Ali, Abdul Basit; Riaz, Iman Ullah; Fatima, Paras; Hussain, Naveed; Noor, Tahreem (Indus Journal of Bioscience Research, 2025)
Background: Hernia repair is among the most commonly performed surgical procedures worldwide, with mesh reinforcement being the standard of care to reduce recurrence rates. Objective: To compare the postoperative outcomes, complication profiles, and recurrence rates associated with different mesh types used in hernia repair. Methods: A comparative cross-sectional analytical study was conducted at Sheikh Zayed Hospital, Lahore from January 2023-January 2025, including 175 patients undergoing elective hernia repair with mesh placement, using non-probability consecutive sampling. Intraoperative variables such as operative time and estimated blood loss were documented by the surgical team. Postoperative outcomes, including pain (measured using the Visual Analog Scale), seroma formation, wound infection, and recurrence, were assessed during hospital stay and followed up at regular intervals up to 6 months. Results: Out of 175 patients undergoing elective hernia repair, the polypropylene group had the shortest operative time (mean: 58.4 minutes) but the highest recurrence rate (7.1%) and postoperative pain incidence (24.3%). Polyester mesh showed a moderate recurrence rate (5.5%) and the highest infection rate (12.7%). Composite mesh had the lowest recurrence (2.0%) and minimal postoperative pain (16.0%), though it required a slightly longer operative time (65.1 minutes). Overall, composite mesh provided the most favorable balance between safety and efficacy. Conclusion: It is concluded that while polypropylene mesh remains a cost-effective option, composite mesh offers superior outcomes with fewer complications and significantly lower recurrence rates. Mesh selection should be individualized based on patient factors, surgical goals, and long-term outcome priorities.